1993
DOI: 10.1540/jsmr.29.81
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a new Colonic Prokinetic Compound, T-1815, on Gastrointestinal Motility in Anesthetized and Conscious Fasted Dogs.

Abstract: Effect of T-1815, a new colonic prokinetic compound, on gastrointestinal motility was studied in anesthetized and conscious dogs fasted for 24 hr before experiment.In anesthetized dogs, intravenous injection of T-1815 in doses of 0.3-3.0 mg/kg caused a biphasic effect on the gastric motility, a slight decrease followed by a slight increase. While the compound elicited only an increase in motility of the duodenum, jejunum and colon. In the colon, high- From the above results, it is concluded that the pharmacolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Bethanechol (Urecholine; Merck, West Point, PA) was administered at a dose of 2.5, 5, or 10 mg subcutaneously, because intravenous administration is contraindicated in humans. Prior studies in humans demonstrated that these doses are safe, enhance bladder contractility (21), and encompass the dose (0.05 mg/kg sc) that increased colonic motor activity in dogs (33). The subcutaneous dose used clinically to relieve postoperative ileus and abdominal distension is 5 mg (28,29).…”
Section: Drugsmentioning
confidence: 99%
“…Bethanechol (Urecholine; Merck, West Point, PA) was administered at a dose of 2.5, 5, or 10 mg subcutaneously, because intravenous administration is contraindicated in humans. Prior studies in humans demonstrated that these doses are safe, enhance bladder contractility (21), and encompass the dose (0.05 mg/kg sc) that increased colonic motor activity in dogs (33). The subcutaneous dose used clinically to relieve postoperative ileus and abdominal distension is 5 mg (28,29).…”
Section: Drugsmentioning
confidence: 99%